2011
DOI: 10.1055/s-0031-1281515
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Indocyanine Green Fluorescence Angiography in Plastic Surgery

Abstract: In flap reconstruction of complex defects the perfusion of the reconstructive flap is critical to the ultimate success of the reconstruction. This is especially true in perforator-based flaps where it can be difficult to assess the adequacy of perfusion in the operating room. However, the ability to definitively determine the degree of flap perfusion is imperative to clinical decision-making. An emerging technology using near-infrared angiography with indocyanine green (ICG) dye may significantly improve the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 53 publications
0
101
0
Order By: Relevance
“…Use of ICG angiographic imaging has been previously examined for monitoring vascular perfusion in animals and humans, thus forming the foundation of the SPY Imager device that is primarily used to monitor vascular reanastamoses during different surgical procedures (13,16,20,24,29). However, in this study we found that the SPY Imager was very capable and useful for performing serial measurements of vascular perfusion of ICG that allowed for enhanced imaging of vascular remodeling responses in situ over time.…”
Section: Discussionmentioning
confidence: 85%
“…Use of ICG angiographic imaging has been previously examined for monitoring vascular perfusion in animals and humans, thus forming the foundation of the SPY Imager device that is primarily used to monitor vascular reanastamoses during different surgical procedures (13,16,20,24,29). However, in this study we found that the SPY Imager was very capable and useful for performing serial measurements of vascular perfusion of ICG that allowed for enhanced imaging of vascular remodeling responses in situ over time.…”
Section: Discussionmentioning
confidence: 85%
“…It also has a short plasma half-life (three minutes), allowing for repeat evaluation during the same operative procedure [11]. Upon excitation by NIR of 760 nm, ICG has an absorption maximum of 805 nm and an excitation maximum of 835 nm when bound to serum albumin [12].The NIR penetration depth is 3-5 mm. ICG cannot be used in patients who have iodide allergies due to the risk of anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…ICG cannot be used in patients who have iodide allergies due to the risk of anaphylaxis. However, the incidence of anaphylaxis is low at a rate of 1 in 42,000 [12].…”
Section: Discussionmentioning
confidence: 99%
“…[21] To shorten this period, different technique both in animal models and human subjects have been suggested and these include ischemic preconditioning, use of hyberbaric oxygen, perfusion fluorometry, laser Doppler flowmetry and near-infrared laser angiography. [22][23][24][25][26] Early division of forehead flaps as at 4-6 days has been documented with minimal complications. However, it is recommended that early flap division should not be undertaken in active smokers and in patients with bleeding disorders to avoid complications.…”
Section: Discussionmentioning
confidence: 99%